Differences in the relation between bone mineral content and lean body mass according to gender and reproductive status by age ranges - Denova-Gutiérrez, Edgar; Clark, Patricia; Capozza, Ricardo Francisco; Nocciolino, Laura Marcela; Ferretti, Jose Luis; Velázquez-Cruz, Rafael; Rivera, Berenice; Cointry, Gustavo Roberto; Salmerón, Jorge (Journal of bone and mineral metabolism, 2019)
The present study aims: (1) to explore the influence of lean mass (LM) on bone mineral content (BMC), (2) to investigate the pubertal influences on the BMC–LM relation, and (3) to perform Z -score charts of BMC–LM relation, stratified by gender and reproductive status categorized by age ranges. A cross-sectional analysis was conducted using 4001 healthy subjects between 7 and 90 years participating in the Health Workers Cohort Study. Of these, 720 participants were ≤ 19 years, 2417 were women ≥ 20 years, and 864 were men ≥ 20 years. Using Dual X-ray absorptiometry (DXA), we measured BMC and LM. Participants’ pubertal development was assessed according to Tanner’s stage scale. To describe BMC–LM relation, simple correlation coefficients were computed. To produce best-fit equations, an ANOVA test was conducted. Z -score graphs for the BMC–LM relation were obtained. In general, the BMC–LM correlations were linear and highly significant. For boys, curves were virtually parallel, with similar intercepts and a progressive displacement of values toward the upper-right region of the graph, for each Tanner subgroup. For girls, curves for Tanner 1-2 and 4-5 stages were parallel; but, in girls Tanner 4-5, the intercepts were significantly higher by about +300–400 g of BMC ( P < 0.001). For postmenopausal women, the curve was parallel to that for the premenopausal but showed a lower intercept ( P < 0.001). We provide DXA reference data on a well-characterized cohort of 4001 healthy subjects. These reference curves provide a reference value for the assessment and monitoring of bone health in all age groups included in the present study.